2011
DOI: 10.1038/jhg.2010.166
|View full text |Cite
|
Sign up to set email alerts
|

No association between TNFSF15 and IL23R with ulcerative colitis in Koreans

Abstract: Recent genome-wide association studies have shown that some Crohn's disease (CD)-associated loci also contribute to ulcerative colitis (UC) susceptibility. To understand the genetic relationship between the two forms of inflammatory bowel disease, we investigated the well-established CD-susceptibility genes TNFSF15 (tumor necrosis factor ligand superfamily, member 15) and IL23R in Korean patients with UC. Eight TNFSF15 and five IL23R single-nucleotide polymorphisms were genotyped in 654 patients with UC and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 37 publications
0
16
1
Order By: Relevance
“…However, the reports of TNFSF15 association with UC in Caucasians have been inconsistent Wang et al, 2010;Haritunians et al, 2010). In contrast to his own previous finding, Yang et al, 2011 reported no association between TNFSF15 and IL23R with UC in Koreans. However, TNFSF15 showed a marginal association with UC in male patients only.…”
Section: Tnfsf15 (9q32)contrasting
confidence: 51%
“…However, the reports of TNFSF15 association with UC in Caucasians have been inconsistent Wang et al, 2010;Haritunians et al, 2010). In contrast to his own previous finding, Yang et al, 2011 reported no association between TNFSF15 and IL23R with UC in Koreans. However, TNFSF15 showed a marginal association with UC in male patients only.…”
Section: Tnfsf15 (9q32)contrasting
confidence: 51%
“…A part of this cohort has been studied previously, and determination of phenotypic subgroups of UC was described before. 33,34 Of 1198 patients with UC, 998 were diagnosed at the IBD Clinic of Asan Medical Center, 151 from the Kyung Hee University Hospital, and 49 from the Ewha Womans University Mokdong Hospital, Seoul, Korea, on the basis of conventional clinical, radiologic, endoscopic, and histopathologic criteria. Control subjects for the first stage were from the population control data.…”
Section: Study Populationmentioning
confidence: 99%
“…[23][24][25][26][27][28][29] The TNFSF15 variants contributed to the susceptibility for UC and CD in European populations 8,30 but only for CD in Asians. [31][32][33] So far, only a few studies of UC susceptibility loci have been reported in Asian cohorts. 17,34 One GWAS of UC has been reported in a Japanese population, 17 identifying 5 UC susceptibility genes, which overlapped with the 47 published risk loci in Caucasians.…”
mentioning
confidence: 98%
“…Most of the remaining CD susceptibility loci have not been subjected to validation study in Asian populations. TNFSF15 also showed association with ulcerative colitis (UC), another form of IBD, in Caucasians,8 25 but not in Asians 26 28. As previous Asian studies, including one GWAS, tested rather a limited number of candidate single nucleotide polymorphisms (SNPs) in small sample sizes, additional GWAS in Asians would be helpful to find remaining risk loci and narrow down causative loci by trans-ethnic mapping.…”
Section: Introductionmentioning
confidence: 99%